2003
DOI: 10.1128/aem.69.12.7492-7498.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Glycine Betaine and Carnitine Transporters in Adaptation of Listeria monocytogenes to Chill Stress in Defined Medium

Abstract: The food-borne pathogen Listeria monocytogenes proliferates at refrigeration temperatures, rendering refrigeration ineffective in the preservation of Listeria-contaminated foods. The uptake and intracellular accumulation of the potent compatible solutes glycine betaine and carnitine has been shown to be a key mediator of the pathogen's cold-tolerant phenotype. To date, three compatible solute systems are known to operate in L. monocytogenes: glycine betaine porter I (BetL), glycine betaine porter II (Gbu), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 49 publications
3
68
0
6
Order By: Relevance
“…It is likely that accumulation of these compounds is driven by three ABC uptake systems (LSA0616 to LSA0619, LSA1694 to LSA1696, LSA1869-LSA1870), together with a Na + -dependent symporter (LSA0264). This genetic repertoire is similar to that found in Listeria monocytogenes, an organism also known for salt and cold resistance 20,21 . Similarly, L. sakei has more putative cold stress proteins (LSA0768, LSA0946, LSA1152, LSA1561) than other lactobacilli, but as many as L. monocytogenes.…”
Section: General Metabolism and Meat Adaptationsupporting
confidence: 72%
“…It is likely that accumulation of these compounds is driven by three ABC uptake systems (LSA0616 to LSA0619, LSA1694 to LSA1696, LSA1869-LSA1870), together with a Na + -dependent symporter (LSA0264). This genetic repertoire is similar to that found in Listeria monocytogenes, an organism also known for salt and cold resistance 20,21 . Similarly, L. sakei has more putative cold stress proteins (LSA0768, LSA0946, LSA1152, LSA1561) than other lactobacilli, but as many as L. monocytogenes.…”
Section: General Metabolism and Meat Adaptationsupporting
confidence: 72%
“…There are many transporters known to mediate bacterial stress responses and virulence through the uptake of compatible solutes, low molecular weight osmolytes that can be accumulated to high concentrations without interfering with cellular processes [19]. In Listeria monocytogenes, the ABC transporters Gbu and OpuC, which are homologous to BilE, as well as the functionally related secondary transporter BetL, contribute to osmo-, bile-and chill-tolerance by importing glycine betaine and carnitine [16,[20][21][22]. Although it was initially hypothesized that BilE (then called OpuD) was an additional compatible solute transporter, it has since been demonstrated that it is unable to mediate transport of glycine betaine, carnitine, or choline (a metabolic precursor of glycine betaine), and plays no role in osmo-or chill-tolerance [18].…”
Section: Introductionmentioning
confidence: 99%
“…The third response may also involve regulation at the level of protein activity, at least as far as uptake of compatible solutes is concerned. These phenomena have been studied in great detail in L. monocytogenes (4,5,48). To date, three uptake systems for compatible solutes are known in this bacterium, both a primary (Gbu) and a secondary (BetL) betaine carrier as well as the primary carnitine transporter OpuC (4).…”
mentioning
confidence: 99%
“…Chill stress response in bacteria includes at least three different mechanisms, synthesis of so-called cold shock proteins (6,7), synthesis of branched-chain and unsaturated fatty acids (2,21,26,45,47), and uptake and synthesis of compatible solutes (4,23). The first two types of response necessarily involve regulation at the level of expression and have been studied in detail in Escherichia coli, Bacillus subtilis, and Listeria monocytogenes (1,2,11,15,18,19,20,32,33,41,45,46,50).…”
mentioning
confidence: 99%